Porphyrin biosynthesis in Rhodopseudomonas palustris-IX. PBG-deaminase. Kinetic studies - Kotler, M.L. (1987)
1. 1. PBG-Deaminase obtained from Rp. palustris exhibited classical Michaelis-Menten kinetics in the absence or presence of different ions. 2. 2. Detailed kinetic studies were carried out in the presence of ammonium, phosphate and magnesium ions. 3. 3. It has been found that the different effects observed are dependent on both the substrate and the ion concentration. © 1987.